THE POSSIBILITY OF ASSESSING BALANCE THE AUTONOMIC NERVOUS SYSTEM IN PATIENTS WITH PERSISTENT ATRIAL FIBRILLATION - Soloviov, O.V. (World of Medicine and Biology, 2013)
The relevance of the study of atrial fibrillation (AF), primarily due to the fact that the presence of cardiac arrhythmias significantly increases the relative risk of total and cardio - vascular mortality. Currently AF is considered as a potentially lethal arrhythmia, given the wide range of its negative consequences associated not only with a significant deterioration in the quality of life, but also a significant increase in the frequency of serious complications and death. When a patient with AF increased risk of stroke, and mortality is approximately 2 times higher than individuals with sinus rhythm. The occurrence of frequent paroxysms of AF contributes to the electrical and anatomical remodeling of the myocardium and reduces the contractile function of the heart, increases the incidence of thromboembolic complications, overall mortality and reduces the quality of life for patients. Despite more than a century of study of phase transitions and a large amount of accumulated data, many questions regarding the pathogenesis of AF are still poorly understood. In particular, the issues related to the role of ANS in the pathogenesis of this arrhythmia. Scientific and practical relevance of the search for answers to these questions is no doubt, as a more precise knowledge of the characteristics of the pathogenesis of AF may open new avenues to treat it. This determines the need for further research in this area.